2015
DOI: 10.1038/srep14953
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking GPR3 receptors display late-onset obese phenotype due to impaired thermogenic function in brown adipose tissue

Abstract: We report an unexpected link between aging, thermogenesis and weight gain via the orphan G protein-coupled receptor GPR3. Mice lacking GPR3 and maintained on normal chow had similar body weights during their first 5 months of life, but gained considerably more weight thereafter and displayed reduced total energy expenditure and lower core body temperature. By the age of 5 months GPR3 KO mice already had lower thermogenic gene expression and uncoupling protein 1 protein level and showed impaired glucose uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 56 publications
(65 reference statements)
3
28
0
Order By: Relevance
“…Glucose tolerance and insulin sensitivity tests were performed as described previously (24). HOMA-IR was calculated as follows: fasting insulin (μU/mL) × fasting glucose (mg/dL)/405 (25).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose tolerance and insulin sensitivity tests were performed as described previously (24). HOMA-IR was calculated as follows: fasting insulin (μU/mL) × fasting glucose (mg/dL)/405 (25).…”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic relation of GPR3, GPR6 and GPR12 with the cannabinoids attracted researchers to explore the role of these orphan receptors in metabolic disorders. Thus far, only one study has shown a relation between GPR3 and late-onset obesity, whereas diverse reports have examined how GPR12 interplays in these pathologies (Bjursell et al 2006; Frank et al 2012; Godlewski et al 2015). A patent also claimed the use of GPR6 inverse agonists in the treatment of obesity (Beeley et al 2001).…”
Section: Biological Relevancementioning
confidence: 99%
“…Kunos and coworkers identified a link between GPR3 weight gain and thermogenesis in old mice (Godlewski et al 2015). In these studies, mice lacking GPR3 and maintained on standard chow diet showed an obese phenotype after 5 months of life.…”
Section: Biological Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, different researchers have demonstrated its ability to modulate amyloid-beta production suggesting that it may play a critical role in Alzheimer’s disease (Huang et al, 2015; Nelson & Sheng, 2013; Thathiah et al, 2009, 2013). In addition, GPR3 has been reported to promote neurite outgrowth (Tanaka et al, 2014; Tanaka, Ishii, Kasai, Sung, & Saeki, 2007; Tanaka, Shaikh, Chiocca, & Saeki, 2009), to regulate meiotic prophase arrest in oocyte maturation (Mehlmann et al, 2004), alter emotional behaviors (Valverde et al, 2009), to modulate early phases of cocaine reinforcement (Tourino et al, 2012), to control neuropathic pain after peripheral nerve injury (Ruiz-Medina, Ledent, & Valverde, 2011) and to be involved in age-related obesity (Godlewski et al, 2015). All these data indicate that GPR3 represents a potential therapeutic target for the treatment of a variety of physiopathological conditions.…”
Section: Introductionmentioning
confidence: 99%